The Using of Means of the Information-Communication Technologies in the Educational Process of the Institutions of Higher Education - Ihor Zaitsev (Pedagogical Discourse, 2017)
In the proposed article, the author attempts, based on the analysis of normative legal documents, researches of modern scholars, as well as requests of the practice of higher education institutions to reveal the key aspects of the use of information and communication technologies in the educational process of higher education institutions. On the basis of the analysis of state documents, the essence of the definition of information means, which is interpreted as electronic computers, software, mathematical, linguistic and other support, information systems or their individual elements, information networks and communication networks used for the implementation of information technologies are disclosed.The essence of information and communication technologies, as well as factors influencing the use of information and communication technologies in education, is established. The list of means of information and communication technologies (hardware and software) is indicated. The forms of work at the lessons in higher education institutions are presented, as well as the ways of using information and communication technologies in higher education institutions. The conclusion is made on the expediency and effectiveness of the use of information and communication technologies in the educational process of institutions of higher education.